SYNTHESIS AND STABILITY INVESTIGATION OF MESO HYDROXY ACYL DIPYRROMETHANE STRUCTURE - Akbar Ferryansyah , Mohammad
Dipyrromethane (DPM) is generally used as a precursor for functional organic compounds such as dipyrrin and in the synthesis of porphyrins. DPM can be oxidized to produce dipyrrin, but under certain conditions, a side reaction occurs which produces the meso-hydroxy compound dipyrromethane. This compound is reported to be able to form a complex with zinc(II) ions and has the potential to become a fluorescence-based zinc(II) ion sensor. In this research, meso hydroxy acyl dipyrromethane compounds were synthesized and spectroscopic and computational studies were carried out to explain the possible mechanism for the formation and stability of meso hydroxy acyl dipyrromethane compounds. The synthesis of meso-hydroxy acyl dipyrromethane compounds was carried out in three stages, namely synthesis of dipyrromethane from pyrrole and aldehyde, then acylation of dipyrromethane, then oxidation of acyl dipyrromethane using a DDQ catalyst (2,3-dichloro-5,6-dicyano-1,4-benzoquinone). The meso-hydroxy compound bis(p anisoyl)-p-fluorophenyl dipyrromethane (3-OH) was successfully synthesized from p fluorobenzaldehyde with a total yield of 4.3%. Spectroscopic studies include 1H-NMR, MALDI MS, and UV-vis spectroscopy studies. In computational studies, molecular structure optimization, electronic structure determination and thermochemical parameters were carried out. After complexation of 3-OH with zinc(II) to produce the Zn-3 complex, changes in the 1H-NMR spectrum were found, namely deshielding of the pyrrole signal and loss of the OH-meso signal. The MS spectrum of 3-OH and Zn-3 shows the 3-Dip peak, which is the stable dipyrin species of 3-OH after releasing H2O. UV-vis spectrum measurements indicated that complexation of 3-OH with Zn(II) gave rise to a new peak at 567 nm and decreased intensity at 325 nm, in accordance with the results of electronic transition calculations. Thermochemical computational studies show that 3-OH is more unstable than 3-Dip so that the reaction of 3-Dip to 3-OH is not spontaneous. However, the Zn-3 complex has a lower chemical potential, indicating that the complexation of 3 OH with Zn(II) is highly thermochemically favored despite relatively slow kinetics. The existence of the 3-OH species is thought to be a side reaction of a first-order nucleophilic substitution by H2O as a nucleophile on the cationic acyl dipyrromethane (kat-2a) species.